PELATIHAN DAN PENDAMPINGAN PENYUSUNAN KURIKULUM OPERASIONAL SATUAN PENDIDIKAN (KOSP) BERBASIS KURIKULUM MERDEKA - Mastikawati, Mastikawati; Fitriah, Fitriah; Azwir, Azwir (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
The curriculum is a system that includes objectives, content, evaluation and others that are interrelated in schools to obtain the expected results in and out of school situations. The independent curriculum comes as a national curriculum part of the new paradigm learning launched by the Ministry of Education, Culture, Research and Technology. This research aims to help increase understanding of the Merdeka Curriculum and train kindergarten teachers in designing learning based on the Merdeka Curriculum in PAUD. This training and assistance uses lecture, discussion and simulation methods. The result of this service is that there is an average increase of 7% to 43%. Based on this, it can be concluded that the Operational Curriculum Preparation Training is important to be carried out to provide knowledge to PAUD teachers on how to implement the independent curriculum in each unit, how to make teaching modules and learning evaluations and strengthen the profile of Pancasila students in early childhood.